THE EFFECTIVENESS OF INTERNAL DEVALUATION IN LITHUANIA AND LATVIA - Medaiskytė, Rūta; Klyvienė, Violeta (Ekonomika, 2012)
In the face of economic crisis, Baltic governments had to choose between internal and actual devaluation. Eventually, the first path was chosen to tackle the external and domestic macroeconomic instability. The aim of this study was to evaluate the effectiveness of the internal devaluation policy in the Baltic economies. Using qualitative research methods and graphical analysis, we have evaluated whether the choice of internal devaluation or deflation was appropriate in the exceptional recession period and whether it helped to eliminate the imbalances of the boom period. Obviously, fiscal consolidation helped to ease the tensions and restore confidence in the markets. However, we believe that the internal devaluation policy was efficient only temporarily in Latvia and Lithuania. This policy was hampered by the sectorial mismatches between labour demand and supply, which resulted from a strong surge in unemployment. A. detailed cos–benefit analysis of the internal devaluation policy option requires a more formal econometric analysis which will be implemented in the future research.